Transitional Blended Realities: Linking between Video and Mixed Reality for Distributed Team Collaboration - Gronbak, Jens Emil (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2023)
This paper envisions Transitional Blended Realities (TBR)-systems that integrate interfaces for Video Conferencing and Collaborative Mixed Reality. By utilizing a visual overlap in the reference space between remote physical spaces, TBR supports fluid transitions between video conferencing and mixed reality collaboration. This approach has the potential to enhance both collaboration flexibility and accessibility, fostering more dynamic distributed team meetings.